Pengentasan Kemiskinan Melalui Pemberdayaan Ekonomi Umat Menurut Persfektif Islam - Istan, Muhammad (AL-FALAH : Journal of Islamic Economics, 2017)
Poverty as a social problem will never escape the attention and discussion of Islamic teachings. Islam explores some of the most urgent main themes of empowerment and community involvement in eradicating their poverty. The Quran as the main source of Islamic teachings echoed a moral call for social justice in the economy to be upheld against people living below the poverty line. Efforts to alleviate poverty, one of the main focuses in Islam is the doctrine of weak economic empowerment of the people. Islam considers human resources personally to be the main agent in empowering the peoples economy. Furthermore, Islam also sees that poverty alleviation is the collective responsibility of society so that the effort of economic empowerment of the poor becomes the collective obligation of all elements of society, especially poverty caused by social structure. It takes synergy between elements of society both government, ulama and society itself as subject and object of change. Some of the above empowerment models can be divided into two groups; Structural and cultural measures. Structural measures are more emphasized to the special institutions that handle them to run well, while cultural steps are emphasized on individuals, both individuals who are expected to be one of the subjects of poverty alleviation and empowerment of the poor and the poor and who became its object